Methodology for Preparing the General Physical Condition of Young Volleyball Players in the Existing Conditions in the Republic (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2023)
The article discusses issues related to the methodology of training young volleyball players in modern conditions. The author focuses on the versatile physical and technical training of children based on mastering the elements of volleyball and other sports.